2010
DOI: 10.1016/j.neurobiolaging.2008.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Medial septal β-amyloid 1-40 injections alter septo-hippocampal anatomy and function

Abstract: Degeneration of septal neurons in Alzheimer's disease (AD) results in abnormal information processing at cortical circuits and consequent brain dysfunction. The septum modulates the activity of hippocampal and cortical circuits and is crucial to the initiation and occurrence of oscillatory activities such as the hippocampal theta rhythm. Previous studies suggest that amyloid β peptide (Aβ) accumulation may trigger degeneration in AD. This study evaluates the effects of single injections of Aβ 1-40 into the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 61 publications
4
33
0
3
Order By: Relevance
“…An examination of the local microenvironment around A␤ deposits in the hippocampus confirms that focal A␤40 and A␤42 injections in rats trigger long-lasting microglial activation (Weldon et al, 1998;Stéphan et al, 2003;Colom et al, 2010), as observed in the brain of AD patients (for review, see Akiyama et al, 2000). This microglial activation contributes to neuronal alterations, including a local loss of dendritic spines and axonal dystrophy, as well as modifications in the functional properties of neurons (Busche et al, 2008;Meyer-Luehmann et al, 2008).…”
Section: Discussionmentioning
confidence: 65%
“…An examination of the local microenvironment around A␤ deposits in the hippocampus confirms that focal A␤40 and A␤42 injections in rats trigger long-lasting microglial activation (Weldon et al, 1998;Stéphan et al, 2003;Colom et al, 2010), as observed in the brain of AD patients (for review, see Akiyama et al, 2000). This microglial activation contributes to neuronal alterations, including a local loss of dendritic spines and axonal dystrophy, as well as modifications in the functional properties of neurons (Busche et al, 2008;Meyer-Luehmann et al, 2008).…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, we analyzed immunoreactivity to NeuN, which is a general neuronal marker, (Colom et al, 2010) and Syn2 in the cortex, hippocampus and CPu. Syn2 is a presynaptic vesicle protein located in axons (Tarsa and Goda, 2002) and its increased level is correlated to improvement of cognitive function in rodents (Mulder et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although in this work, we only focus on the system dynamical changes caused by the pathological changes in the hippocampal pyramidal neurons, it should be admitted that the Aβ-indued hippocampal dysfunction may be more complex. For example, it has been shown in (Villette et al 2010;Colom et al 2010) that Aβ-induced GABAergic and cholinergic system degeneration in the medial septum may also cause hippocampal dysfunctions. GABAergic neurons inhibit hippocampal OLM and basket neurons and act as a hippocampal theta rhythm pacemaker and cholinergic neurons control the acetylcholine level in the hippocampus, which can change the dynamics of pyramidal neurons and synapses.…”
Section: Discussionmentioning
confidence: 99%